2018
DOI: 10.3390/nu10010077
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbohydrate, High-Protein, High-Fat Diets Rich in Livestock, Poultry and Their Products Predict Impending Risk of Type 2 Diabetes in Chinese Individuals that Exceed Their Calculated Caloric Requirement

Abstract: The evidence on the association between long-term low-carbohydrate, high-fat and high-protein diets and type 2 diabetes (T2D) is controversial. Until now, data is limited for Chinese populations, especially in considering the influence of extra energy intake. In this paper, we aimed to investigate the association of low-carbohydrate, high-fat and high-protein diets with type 2 diabetes (T2D) risk in populations consuming extra calories and those with normal caloric intake, We also determined whether the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…To the best of our knowledge, our study is the first meta-analysis to identify an association of poultry intake with the risk of T2D. The subgroup analysis and a recent study both showed a protective effect of poultry intake on the development of T2D in China [84]. Regional differences in the relationship between white meat intake and diabetes may be related to the distinct in cooking styles between China and Europe, particularly in regard to frying versus boiled or steamed meat.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, our study is the first meta-analysis to identify an association of poultry intake with the risk of T2D. The subgroup analysis and a recent study both showed a protective effect of poultry intake on the development of T2D in China [84]. Regional differences in the relationship between white meat intake and diabetes may be related to the distinct in cooking styles between China and Europe, particularly in regard to frying versus boiled or steamed meat.…”
Section: Discussionmentioning
confidence: 99%
“…A validated semi-quantitative food frequency questionnaire and 24 h recall method for the last three consecutive days (two weekdays and one weekend day) were used to collect data regarding dietary intake. In the present study, we only considered the intake of cereals and beans, and the intake of meat and poultry as confounders, as they have been found to be associated with type 2 diabetes [ 20 , 21 ]. The Chinese Dietary Guideline recommends that the reference intake of meat and poultry is between 40 g and 75 g, and the reference intake of cereals and beans is between 50 g and 150 g [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Family history of diabetes was defined as those whose first-degree relatives suffered from diabetes. The presence of coronary heart disease at baseline was collected by using a structured questionnaire [17].…”
Section: Questionnaire Surveymentioning
confidence: 99%